On Doctors, Mechanics, and Computer Specialists: The Economics of Credence Goods - Dulleck, Uwe; Kerschbamer, Rudolf (Journal of Economic Literature, 2006)
Most of us need the services of an expert when our apartment's heating or our washing machine breaks down, or when our car starts to make strange noises. And for most of us, commissioning an expert to solve the problem causes concern. This concern does not disappear even after repair and payment of the bill. On the contrary, one worries about paying for a service that was not provided or receiving some unnecessary treatment. This article studies the economics underlying these worries. Under which conditions do experts have an incentive to exploit the informational problems associated with markets for diagnosis and treatment? What types of fraud exist? What are the methods and institutions for dealing with these informational problems? Under which conditions does the market provide incentives to deter fraudulent behavior? And what happens if all or some of those conditions are violated?